INNOVATIVE TECHNOLOGIES IN TEACHING TRANSPORT TERMINOLOGY (International Conference on Modern Science and Scientific Studies, 2025)
Transport is one of the most important sectors of the economy of any country, the level of development of which largely determines the well-being of society as a whole, it is not only a means of carrying out domestic and foreign economic activity, but also an infrastructural support that supports social policy and ensures the integrity of the state, nation. This is especially true for a country like Uzbekistan. Transport is a complex diversified economy, which includes: vehicles; roads; communication routes with the necessary track devices; facilities for the repair, maintenance of vehicles. Transport activity is formed in the system of five types of transport: rail, road, water (sea, river), air and pipeline. Transport and objects of its infrastructure are subject to classification on various grounds.